Formulation and Evaluation of Face Moisturizing Cream from Katuk Leaf Extract (Sauropus Androgynus Merr) - Siallagan, Johnson; Kano, Christina Paulina; Yabansabra, Yuliana Ruth; Pramesti, Santinia Andiva; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Cionita, Tezara; Guterres, Natalino Fonseca Da Silva (Universitas Negeri Semarang, 2024)
The Katuk plant (Sauropus androgynus L. Merr) is a natural substance with proven efficacy in treating diabetes, obesity, and inflammation. It also possesses antioxidant, lactation-inducing, and antibacterial properties. This study aimed to investigate the impact of varying concentrations of katuk leaf extract on characteristics of the moisturizer cream produced. The study involved extracting katuk leaves using the maceration method for 24 hours, utilizing ethanol as the solvent. The extraction process resulted in a yield of 1.86%. The final yield contains alkaloid chemicals, flavonoids, terpenoids, saponins, and tannins. The formulations employed in this investigation utilized the codes F0, F1, F2, and F3, representing the content of katuk leaf extract at 0%, 2%, 4%, and 6%, respectively. The cream generated exhibited an identifiable aroma of katuk and had a hue ranging from light green to blackish brown, as determined by organoleptic testing. The pH values of specimens F0, F1, F2, and F3 were 7, 7, 7, and 8, respectively. The spread ability measurements for specimens F0, F1, F2, and F3 were 5.3 cm, 5.5 cm, 6 cm, and 6.1 cm, respectively. According to the findings of this investigation, specimens F0, F1, F2, and F3 adhered for 5 seconds, 4 seconds, 4 seconds, and 5 seconds, respectively. The formulation F2 is the most superior product generated in this investigation. This is because this specimen exhibits the highest level of respondent satisfaction compared to the other specimens. This formulation exhibits antioxidant activity with a per cent inhibition of 30.51% and an IC50 value of 84.63 ppm. The face moisturizing cream derived from katuk leaf extract possesses a high antioxidant potency, placing it in the active/strong category.